Download presentation

Presentation is loading. Please wait.

Published byBlake Lester Modified over 6 years ago

2
Mr. C Does: Find length of missing side Steps: 1.Pythagorean Theorem 2.Substitute Numbers 3.Exponents 4.Solve for the variable 5.Square Root both sides A 2 + B 2 = C 2 4 2 + B 2 = 5 2 16 + B 2 = 25 -16 B 2 = 9 B = 3 5 4 A B C

3
Students Do: Find length of missing side Steps: 1.Pythagorean Theorem 2.Substitute Numbers 3.Exponents 4.Solve for the variable 5.Square Root both sides A 2 + B 2 = C 2 A 2 + 12 2 = 13 2 A 2 + 144 = 169 -144 A 2 = 25 A = 5 a = ? b = 12 c = 13

4
Error Analysis: Find the mistake and explain it using vocabulary words if possible: Leg, hypotenuse, right angle. a = 6 b = 8 c = ? A 2 + B 2 = C 2 6 2 + B 2 = 8 2 36 + B 2 = 64 -36 B 2 = 25 B= 5

6
START 2:30 5:00

11
1.What techniques did the book used to simplify the polynomial? 2.What type of factoring was used in this example? 3.How did factoring help simplify this rational expression?

13
Apply what you learned from example 2: Simplify. 1. 2. x 2 + 5x + 6 x + 2 x+3 2x 2 + 8x + 8 x 2 + 5x + 6 2(x + 2) (x+3)

14
So to SIMPLIFY rational expressions, factor to see what you can cancel 1.) x + 4. 2x 2 - 2x – 40 = (x + 4). 2(x + 4)(x – 5) = 1 2(x - 5) 2.) 8x + 72. 10x 2 + 100x + 90 = 8(x + 9) 10(x 2 + 10x + 9) = 8(x + 9) 10(x + 9)(x + 1) = 4. 5(x + 1) Reduce! When you cancel it becomes a 1

15
1.) x – 2. x 2 + x – 6 = (x – 2). (x + 3) (x – 2) = 1 x+3 2.) 3x 2 + 9x + 6. 6x 2 + 36x + 30 = 3(x 2 + 3x + 2) 6(x 2 + 6x + 5) = 3(x + 1)(x + 2) 6(x + 5)(x + 1) = (x + 2). 2(x + 5) Reduce! Remember when you cancel it becomes a 1

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google